Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's pair the given circle equations in general form with their corresponding equations in standard form step-by-step.
1. Equation in General Form: [tex]\(x^2 + y^2 - 4x + 12y - 20 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x - 2)^2 + (y + 6)^2 = 60 \)[/tex]
2. Equation in General Form: [tex]\(x^2 + y^2 + 6x - 8y - 10 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x + 3)^2 + (y - 4)^2 = 25 \)[/tex]
3. Equation in General Form: [tex]\(3x^2 + 3y^2 + 12x + 18y - 15 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x + 2)^2 + (y + 3)^2 = 18 \)[/tex]
4. Equation in General Form: [tex]\(5x^2 + 5y^2 - 10x + 20y - 30 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x + 1)^2 + (y - 6)^2 = 46 \)[/tex]
5. Equation in General Form: [tex]\(2x^2 + 2y^2 - 24x - 16y - 8 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x - 6)^2 + (y - 4)^2 = 56 \)[/tex]
So, the correct pairs are:
- [tex]\( x^2 + y^2 - 4x + 12y - 20 = 0 \)[/tex] and [tex]\( (x - 2)^2 + (y + 6)^2 = 60 \)[/tex]
- [tex]\( x^2 + y^2 + 6x - 8y - 10 = 0 \)[/tex] and [tex]\( (x + 3)^2 + (y - 4)^2 = 25 \)[/tex]
- [tex]\( 3x^2 + 3y^2 + 12x + 18y - 15 = 0 \)[/tex] and [tex]\( (x + 2)^2 + (y + 3)^2 = 18 \)[/tex]
- [tex]\( 5x^2 + 5y^2 - 10x + 20y - 30 = 0 \)[/tex] and [tex]\( (x + 1)^2 + (y - 6)^2 = 46 \)[/tex]
- [tex]\( 2x^2 + 2y^2 - 24x - 16y - 8 = 0 \)[/tex] and [tex]\( (x - 6)^2 + (y - 4)^2 = 56 \)[/tex]
1. Equation in General Form: [tex]\(x^2 + y^2 - 4x + 12y - 20 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x - 2)^2 + (y + 6)^2 = 60 \)[/tex]
2. Equation in General Form: [tex]\(x^2 + y^2 + 6x - 8y - 10 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x + 3)^2 + (y - 4)^2 = 25 \)[/tex]
3. Equation in General Form: [tex]\(3x^2 + 3y^2 + 12x + 18y - 15 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x + 2)^2 + (y + 3)^2 = 18 \)[/tex]
4. Equation in General Form: [tex]\(5x^2 + 5y^2 - 10x + 20y - 30 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x + 1)^2 + (y - 6)^2 = 46 \)[/tex]
5. Equation in General Form: [tex]\(2x^2 + 2y^2 - 24x - 16y - 8 = 0\)[/tex]
- Corresponding Equation in Standard Form: [tex]\( (x - 6)^2 + (y - 4)^2 = 56 \)[/tex]
So, the correct pairs are:
- [tex]\( x^2 + y^2 - 4x + 12y - 20 = 0 \)[/tex] and [tex]\( (x - 2)^2 + (y + 6)^2 = 60 \)[/tex]
- [tex]\( x^2 + y^2 + 6x - 8y - 10 = 0 \)[/tex] and [tex]\( (x + 3)^2 + (y - 4)^2 = 25 \)[/tex]
- [tex]\( 3x^2 + 3y^2 + 12x + 18y - 15 = 0 \)[/tex] and [tex]\( (x + 2)^2 + (y + 3)^2 = 18 \)[/tex]
- [tex]\( 5x^2 + 5y^2 - 10x + 20y - 30 = 0 \)[/tex] and [tex]\( (x + 1)^2 + (y - 6)^2 = 46 \)[/tex]
- [tex]\( 2x^2 + 2y^2 - 24x - 16y - 8 = 0 \)[/tex] and [tex]\( (x - 6)^2 + (y - 4)^2 = 56 \)[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.